First modeling of strongly radiating WEST plasmas with SOLEDGE-EIRENE. (August 2019) - Ciraolo, G.; Thin, A.; Bufferand, H.; Bucalossi, J.; Fedorczak, N.; Gunn, J.P.; Pascal, J.Y.; Tamain, P.; Gil, C.; Gouin, A.; Meyer, O.; Devynck, P.; et al.
Highlights: SOLEDGE2D-EIRENE simulations for highly radiating WEST plasmas. Oxygen impurity. First comparison with experimental data. Abstract: We present first results of SOLEDGE-EIRENE modeling a strongly radiating plasma in the WEST tokamak. Using measurements from a reciprocating Langmuir probe we have determined the SOLEDGE input parameters, i.e. separatrix density at outboard midplane and radial transport coefficients typical of L-mode plasma. We have performed deuterium plasma simulations with presence of oxygen, injected from the core boundary into the simulation domain. The comparison between the radiated power measured from the bolometry in the divertor region and the one computed from SOLEDGE simulations seems to indicate a concentration of oxygen of about 2%. Moreover we have obtained good agreement between simulation results and experimental measurements on electron density and electron temperature profiles at the outer strike point. First qualitative analysis of spectroscopic synthetic diagnostic on Dα signals is also presented.